Pemanfaatan Komoditas Jagung menjadi Olahan Emping untuk Peningkatan Nilai Ekonomi Keluarga Desa Panduman Kabupaten Jember - Tjendani, Endah Nur; Rohmah, Ika Habibatur; Khumairoh, Sinta; Dijaya, Pasa; Shaddam, Muhammad Faqih Ubaidillah; Amadea, Mahsa Rifandi Savero; Zahro, Fatimatus (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Corn (Zea mays L) is a crop that is very well known by the Indonesian people and is a staple food in certain areas. The development of corn-based food can be made into emping that has a potential to be eaten by anyone without fear of the certain diseases risk. Panduman Village is a producer of corn, besides of tobacco and rice which are usually sold directly in raw product, for this reason it is very important to carry out community service to increase economic value by making corn flakes traditionally by housewives. The training material classified into how to make corn emping, packaging, and marketing strategies by applying the learning by doing and FGD methods. The results of the community services achieved by housewives in Panduman Village are they were able to make emping with many different tastes (salty, sweet, tasty), packaging and marketing strategies and corn has added economic value.